Organizações e reivindicações indígenas no Brasil central - Antonio H. Aguilera Urquiza; Nataly Guimarães Foscaches; Valdir A. do Nascimento (Les Cahiers ALHIM)
The present work is located in the Center-West region of Brazil and seeks to discuss the reality of the Guarani people and their effective participation in indigenous organizations created since the 1980s and pushed with the approval of the new Federal Constitution (1988). Along with other indigenous peoples, the Guarani seek to operationalize the defense of the rights conquered and to conquer, with emphasis on the expansion of their territories. In this process, there is currently an established relationship between these demands and political organization and the new technologies, driven by the Guarani, specifically the younger ones, as instruments of registration and help to give visibility to their struggles. The aim of this text, the fruit of field research and the authors' experience, was to understand how the demands of the Guarani people are articulated and the appropriation and mastery of new technologies to benefit their causes in the context of indigenous organizations. Fieldwork of ethnographic character was carried out in several Guarani areas, especially in the Pirakuá Village in Bela Vista / MS, a border between Brazil and Paraguay. Participant observation, interviewing and bibliographical and documentary analysis were the methodological tools used to capture and interpret the data presented.